The Model of Customer Misbehavior of Café Employees on Brand Commitment - Maryam Hafidzah; Popy Rufaidah (International Journal of Economics Development Research (IJEDR), 2024)
In the service industry, customer misbehavior is common. Disrespectful behavior in the workplace is common and employees often receive disrespectful treatment from customers. The purpose of this study was to find out the effect of bad behavior by customers on employee brand commitment. Mix Method (Quantitative and Qualitative) is used to maximize research results. The population that becomes the object of this study is cafe employees in Depok City. The number of samples used in this study was 237 respondents. Data was collected by distributing online and offline questionnaires and conducting in-depth interviews with 10 employees. SmartPLS and NVivo were used as software to analyze the data. The results showed that customer misbehavior has a significant negative effect on employee brand commitment. This shows that when the bad behavior from customers received by employees increases, employee brand commitment will decrease.